D. Fr. Aleixo de Meneses (1559-1617): um percurso biográfico em contexto - Olival, Fernanda (2018)
Analysis of the biographical trajectory of Friar Aleixo de Meneses, son of the Portuguese King Sebastião’s schoolmaster and grandson of the 1st Count of Cantanhede. Friar Aleixo joined the Hermits of St. Augustine at the age of 15 and reached the archbishopric, the post of viceroy and the presidency of Portugal’s Council. The article discusses the factors that fostered this rapid promotion and examines if it was unusual in the beginning of the 17th century.